Komunitas Marjinal Pada Masa Pandemi COVID-19: Strategi Adaptasi Individu Transgender di Indonesia - Alaydrus, Sayf; Budianto, Azzah; Artaria, Myrtati; Kaur, Charanjit; Henneberg, Maciej (LIPI Press, 2023)
The COVID-19 pandemic has impacted all walks of life in Indonesia, forcing society to adapt. As one of the gender minority groups in a relatively conservative country, the pandemic might impact the transgender community differently. The purpose of this research is to analyze transgender individuals’ adaptation during the pandemic. We employed the qualitative descriptive research method by conducting in-depth interviews with 10 informants from several cities and regencies in Indonesia. Transcription, categorization, and theoretical review were performed to analyze the data. Our results show that transgender individuals in Indonesia have faced unique difficulties and discrimination during the pandemic, a decrease in income, and limited employment opportunities. Our informants’ adaptation strategies vary, for example, financial planning, socializing with friends, professional counseling, and many more. We conclude that relentless advocacy toward the people and government is required to ensure their rights to equal treatment despite their gender identity. Several suggestions to improve their well-being starts with educating the public to use gender-neutral pronouns, politely asking for people’s pronouns, and understanding transgender issues from their perspective. The government should guarantee antidiscriminative public access, further acknowledge transgender people’s civil rights, and increase social assistance to marginalized communities impacted by the pandemic.